Advanced Materials in Aerospace Engineering : Special topic volume with invited peer reviewed papers only - Bressan, Jose Divo, ditor; Donadon, Mauricio Vicente, ditor (Pfaffikon : Trans Tech Publications Ltd., 2016)
The goal of this special issue is to present the latest findings and promote further research in the areas of advanced materials in aerospace engineering. Nowadays, two related imperatives are influencing the design of aeronautical structures: 1. Requirements for more efficient aircraft (use of advanced lightweight materials, reduction of life cycle costs and particularly operating costs), 2. Requirements to reduce the influence of aircraft on environmental, including the decreasing of gas pollution and noise. Keywords: High Performance Materials, Smart Materials, Composites, Laser Processing, Machining, Structural Integrity, Lightweight Structures, Aerospace Engineering.